EXTREME TRADING VOLUME AND EXPECTED RETURN (Study to Companies Listed in Indonesia Stock Exchange 2008-2012 Period) - Indah Nugraheni, Novita; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2013)
Trading volume has been known as a reliable measurement for stock liquidity. Nevertheless, there are different opinions regarding trading volume and expected return in stocks investment. Wang and Cheng (2004) found that there are differences in expected return between stocks which experience extreme trading volume in where extreme high volume stocks associated with lower expected return than extreme low volume stocks. In contrary, Gervais et. al (2001) found that extreme high volume stocks associated with higher expected return than extreme low volume stocks. This research aims to determine the difference in expected returns between various portfolios sorted based on extreme trading volume. This research conducted on 80 stocks listed in Indonesia Stock Exchange 2008 to 2012 period. This research is conducted following previous researches such as Amihud and Mendelson (1986), Brennan et. al. (1998), Datar et. al. (1998), Gervais et. al. (2001), Wang and Cheng (2004), and Baker and Stein (2004). This research also interacted the extreme trading volume with security characteristics such as past performance, firm size, and Book-to-Market or BM value. The portfolio formation method in this research is referring to return portfolio approach by Gervais et. al. (2001). Using this method, portfolios formed and determined its average expected returns. After that T-test will be performed to determine the difference in expected returns between each contradicting portfolios like extreme high and extreme low volume, extreme high-winner stocks and extreme low-loser stocks, extreme high-large stocks and extreme low-small stocks, and extreme high-glamour stocks and extreme low-value stocks.The results shows that even though the results of all hypotheses testing mathematically support the hypotheses, but the statistically, as calculated by T-Test, there’s no notable different impact of extreme trading volume and security characteristics in Indonesia Stock Exchange. It means that this portfolio strategy does not have significant effect in Indonesia Stock Exchange. This research also found a unique phenomenon in extreme trading volume and expected return study in Indonesia Stock Exchange. Despite the sorting methods, all portfolios showed the same behavior; the average returns chart showed appreciation during 0 week to 1 week of evaluation period but dropped later over the period of 3 weeks before reversal occurred. The phenomena indicated that the market players realized that there are speculations in trading activity which affect the trading volume.